Online distance learning (ODL) among quantity surveying students in Sarawak / Keristina Jangu - Jangu, Keristina (2021)
Distance educators must re-examine teaching and learning concepts as well as challenges of online learning platform during deliver of online programs through online learning platform, because online distance learning seems to have become a transnational and regional phenomena as mentioned by (Rogers & Mayes, 2007). According to Gunawardena, (2013) stated that, the institutions in Sarawak consider the option to continue and to adapt distance online learning approaches to suit the inequitable learning experience among quantity surveying students in Sarawak as mentioned by (Pincas, 2001). The aim of the research is to identify the effectiveness of online distance learning among quantity surveying students in Sarawak. The objectives of this research are to identify the challenges of online distance learning among quantity surveying students in Sarawak. Second objective is to explored the advantages of online distance learning among quantity surveying students in Sarawak and third objective is to determine the solution and effectiveness of online distance learning among quantity surveying students in Sarawak. This study is conducted by using existing literature review and questionnaire that are distributed among quantity surveying students in Sarawak. Reviewing existing literature are from the data collected from books, articles and journals.